The difference of matrix metalloproteinase-9 level in saliva between myofascial pain and disc displacement of temporomandibular joint disorders - Rafni, Elita; Y., Yanwirasti; Darwin, Eriyati; Rikmasari, Rasmi (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2017)
Introduction: Saliva is the type of liquid which contains enzyme, hormone, antibody, constituent microbe, and cytokines. Matrix metalloproteinase-9 (MMP-9) is one kind of proteolysis cellular enzyme in saliva that has a role in inflammation. Saliva is very easy to take and noninvasive treatment, proved efficient for early diagnosis. The purpose of this research was to study the difference MMP-9 level in saliva patient with temporomandibular joint disorders between myofascial pain and disc displacement. Methods: Cross sectional comparative study. The research was carried out at the Prosthodontics Clinic of Arifin Achmad Pekanbaru Hospital and at Biomedical Laboratory of Faculty of Medicine, Universitas Andalas Padang, Indonesia. The saliva samples were taken from 37 myofascial pain patients and 37 disc displacement patients. MMP-9 levels were examined by the Elisa and the data result was analyzed using the t-test. Result: The average value of MMP-9 level of disc displacement was 650.98Â±384.94 pg/mL and myofascial pain was 168.70Â±41.24 pg/mL. There was a significant difference on MMP-9 level in saliva between myofascial pain and disc displacement (p<0.05). Conclusion: The MMP-9 level in saliva of patients with disc displacement of temporomandibular joint disorders was higher than patients with myofascial pain.